Thermoplastic composites for protective appliances in sports - Ng, Bao Yuan (Nanyang Technological University, 2024)
This report delves into the exploration of utilising thermoplastic polyurethane (TPU) and polyester composites for the development of an elbow guard tailored for sports. The significance of this investigation lies in the critical role of protective gear in preventing injuries and facilitating safe participation in physical activities. Existing research in the field of protective appliances has showcased advancements, yet a substantial gap remains in the development of innovative materials and manufacturing techniques that offer enhanced protection while ensuring comfort and flexibility. The primary aim of this project was to ascertain the feasibility of manufacturing an elbow guard with the use of TPU and polyester composites that either matches or exceeds the performance metrics established by commercially available counterparts. This project employed a methodological approach involving the design and construction of a two-piece mould to facilitate the manufacturing process. Polyester and TPU plies were placed within the mould and subjected to the hot-pressing process to form the guard. The main technique of assessing the thermoplastic composite elbow guards' and their commercial equivalents' performance was drop weight impact testing. The purpose was to compare the impact response metrics of the two elbow guards. Through the analysis of these parameters, the goal was to get a thorough conclusion about which elbow guard is superior. This approach aimed to determine which elbow guard alternative was more effective by guaranteeing a direct comparison under the same settings and offering insightful information about the protective qualities and energy absorption effectiveness of each material. Findings indicated that all prototypes outperformed the commercial counterpart in impact resistance. Notably, elbow guard #1 distinguished itself by exceeding commercial guard performance metrics without sustaining damage and being lighter, marking it as the most effective model. This underscores the potential of TPU and polyester composites in developing advanced, lightweight protective sports gear.